Enhanced Hypsochromic Shifts, Quantum Yield, and π-π Interactions, in a meso,β-Heteroaryl-fused BODIPY - Zhao, Ning (J Org Chem, 2017)
We report the synthesis and investigation of an unprecedented 8-heteroaryl-fused BODIPY 4. This compound exhibits enhanced π-π stacking in the solid state, unusually large blue-shifts in the absorbance and emission spectra, and higher quantum yield than its unfused precursor; DFT calculations suggest a small energy gap for 4, and strong electronic communication between the 8-OPh and the BODIPY core.